A Survey of Mass Customization in Practice - Samir Barman; Alejandra E. Canizares (International Journal of Supply Chain Management, 2015)
This paper is a literature review of the application of mass customization (MC) in businesses. We identified businesses that have applied the MC concept to create and deliver both tangible goods and intangible services in order to satisfy their customers needs and expectations. With an explanation of the key MC concepts, the research describes the key elements of MC, such as elicitation, process flexibility, and logistics. We also include a description of the four specific MC approaches: collaborative, adaptive, cosmetic, and transparent. Finally, we conclude that there exist many possible applications of MC that are yet to be explored.